Adventitious Shoot Regeneration from Immature Embryo Explant Obtained from Female Ã Female Momordica dioica - Hoque, A; Hossain, M; Alam, S; Arima, S; Islam, R (Plant Tissue Culture and Biotechnology, 2008)
Higher percentage of adventitious shoots regenerated from the immature embryo explant than that of immature cotyledon of the crosses made between female and female (pollen was collected from induced bisexual flower) of tetraploid kakrol (Momordica dioica) on MS induction medium supplemented with different concentrations and combinations of BAP, NAA and GA3. The best response of shoot proliferation was obtained in embryo explants grown in supplemented with 10.8 mg/l BA, 1.08 mg/l NAA and 0.54 mg/l GA3; whereas, shoot regeneration on cotyledon was achieved on a MS supplemented with 16.2 mg/l BA, 2.7 mg/l NAA and 0.54 mg/l GA3. In both cases shoot primordia emerged continuously. This system exhibited a potential for repeated harvesting of the shoots from the original explant as the latter continued to expand and regenerate new shoots, upon repeated periodical subculturing on to fresh medium. Regenerated shoots were excised from both sources and rooted in MS supplemented with different concentrations of IAA. There was no significant difference of root proliferation rate than their sources. Rooted plantlets were acclimatized successfully and later established in the field for the production of female plant and also evaluation of somaclonal variation. Key words: Immature cotyledon, Immature embryo, Momordica dioica, Organogenesis DOI = 10.3329/ptcb.v17i1.1118 Plant Tissue Cult. & Biotech. 17(1): 29-36, 2007 (June)